Peningkatan Pemahaman Konsep Biologi melaui Penguatan Minat dan Kemandirian Belajar - Evi Widyastuty (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The Influence of Interest and Self-directed Learning on Understanding Biology Concepts. The aim of this study is to determine: 1) The combined influence of interest and self-directed learning on the understanding of Biology concepts among high school students in East Jakarta. 2) The influence of interest in learning on the understanding of Biology concepts among high school students in East Jakarta. 3) The influence of self-directed learning on the understanding of Biology concepts among high school students in East Jakarta. The research method used is correlational survey with multiple regression analysis. The sample used in this study consisted of 62 students from State Senior High Schools 31, 22, and 36. The results of the study concluded that 1) There is a significant combined influence of interest and self-directed learning on the understanding of biology concepts among high school students in East Jakarta. This is evidenced by the significance value (sig.) = 0.004 < 0.05 and F-value = 6.012. 2) There is a significant influence of interest in learning on the understanding of Biology concepts among high school students in East Jakarta. This is evidenced by the significance value (sig.) = 0.019 < 0.05 and t-value = 2.420. 3) There is a significant influence of self-directed learning on the understanding of Biology concepts among high school students in East Jakarta. This is evidenced by the significance value (sig.) = 0.035 < 0.05 and t-value = 2.163.